Variation - University of Malaya, Art Gallery (University of Malaya Art Gallery, 2019)
Artists: Rube Jamal, Ahmed Ghazie; Dymphna Lanjuran, Cole Yap, Kamil Shafie; Hafiz Drahman, Adam Azlan, Irene G. Exhibition Date: 15 September-30 Oktober 2019. Venue: University of Malay Art Gallery.